A Serious Game with Geolocalition to Support Learning ofChildren with Autism and Learning Difficulties - Silva, Salatiel Dantas; Sousa Neto, Ademar França de; Mendes Neto, Francisco Milton; Lima, Rodrigo Monteiro de; Demoly, Karla Rosane do Amaral (Anais do Simpósio Brasileiro de Informática na Educação (SBIE), 2020)
People with Autism Spectrum Disorder (ASD) have characteristicsdescribed as the disability to relate to others, communication disorders, andobsessive concern about what is unchanging. In this sense, this paper aimsto present an application for mobile devices, in a serious game format, whosepurpose is to aid the teaching-learning process of autistic children, also seekingto reduce their isolation tendencies. Also, it shows both ontologies and theMultiagent System integrated into the application. The validation occurred withautism specialists through questionnaires. The results indicate that the proposedapplication presents the potential to reach its objectives.